2015
DOI: 10.1164/rccm.201503-0578oc
|View full text |Cite|
|
Sign up to set email alerts
|

Sustained Benefit from Ivacaftor Demonstrated by Combining Clinical Trial and Cystic Fibrosis Patient Registry Data

Abstract: These findings suggest that ivacaftor is a disease-modifying therapy for the treatment of cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
135
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(142 citation statements)
references
References 28 publications
6
135
0
1
Order By: Relevance
“…When the results of the STRIVE and PERSIST studies are combined, current clinical evidence has documented the efficiency of ivacaftor for up to three years of treatment 19 . Our study showed consistent improvement and stabilization of lung function in a small group of CF adults treated with ivacaftor for up to six years.…”
Section: Discussionmentioning
confidence: 99%
“…When the results of the STRIVE and PERSIST studies are combined, current clinical evidence has documented the efficiency of ivacaftor for up to three years of treatment 19 . Our study showed consistent improvement and stabilization of lung function in a small group of CF adults treated with ivacaftor for up to six years.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Two observational studies have confirmed ivacaftor’s real-world effectiveness: A patient registry study found that lung function declined more slowly among patients using ivacaftor, compared to a control group receiving standard care; and an analysis of private insurance claims found lower rates of hospitalization. 16,17 …”
mentioning
confidence: 99%
“…96 An open label extension study examining ivacaftor in people with at least one G551D mutation enrolled in the two RCTs 20 91 has shown a durable treatment response up to 144 weeks, with no new safety concerns. 97 An observational follow-up study of these patients using CF Foundation registry data up to three years showed that ivacaftor can reduce the rate of FEV 1 decline by about 50% relative CFTR read-through agents Open label pilot studies have shown that both the topical and systemic administration of the aminoglycoside gentamicin can augment chloride transport (based on measurement of nasal potential difference; NPD) in people with cystic fibrosis and at least one nonsense mutation in the CFTR gene. [121][122][123] A placebo controlled crossover trial investigating the topical administration of gentamicin to the nasal epithelium for 14 days was conducted in patients who had one or two stop mutations or were homozygous for the F508del mutation.…”
Section: Related Therapeutic Effectsmentioning
confidence: 99%